The role of death in life : a multidisciplinary examination of the relationship between life and death - Behr, John; Cunningham, Conor, 1972- (James Clarke & Co, 2016)
A diverse collection of essays exploring the connection between life and death from scientific, medical, philosophical and theological perspectives.